The Perception of Academic Staff in Relation to Programme Re-Accreditation in South African Higher Education Institutions - Selesho, Jacob M (EDUCARE, 2010)
ABSTRACT: The perception held by academic staff of programme re-accreditation has been a major problem in Higher Education Institutions. Academics are concerned about the influence of the government in their daily operation, while the government claim that they want to be accountable to the public for money spent on Higher Education Institutions. To a large extent, academics believe that the role of the government amounts to interference rather than being accountable, and that the academic freedom has been violated. The participants of the study were academics from the 23 South African universities. Questionnaires, documentary analysis, and interviews were used as the main data collection instruments. The study revealed that a negative perception amongst academic staff existed with regard to programme re-accreditation. Furthermore, the study also established that it is still difficult for academic staff to identify the difference between the role played by the government (accountability) and their own role (academic freedom). It was interesting to note that although academics want to participate in the programme re-accreditation, however, they still have a fear of failure. Those fears foster a negative re-accreditation concept among academics in the HE. For that matter, academics will create a platform to hide their failure. The article further recommends that the first step in programme re-accreditation should perhaps be in the form of improvement or enhancement of quality.KEY WORDS: Programme re-accreditation and self-evaluation, academic staffsâ perception, role of the government, and improvement or enhancement of the Higher Education quality.===About the Author: Dr. Jacob M. Selesho is the Head of Postgraduate Studies in Education, Central University of Technology (CUT), Free State, Bloemfontein, Republic of South Africa. He can be reached at: jselesho@cut.ac.zaHow to cite this article? Selesho, Jacob M. (2010). âThe Perception of Academic Staff in Relation to Programme Re-Accreditation in South African Higher Education Institutionsâ in EDUCARE: International Journal for Educational Studies, Vol.3(1) August, pp.1-10. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (June 11, 2010); Revised (July 11, 2010); and Published (August 17, 2010).